2021
DOI: 10.3390/cancers13040596
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells: Multitasking Cells in the Duty of Cancer Immunotherapy

Abstract: Cancer immunotherapy activates the immune system to specifically target malignant cells. Research has often focused on CD8+ cytotoxic T cells, as those have the capacity to eliminate tumor cells after specific recognition upon TCR-MHC class I interaction. However, CD4+ T cells have gained attention in the field, as they are not only essential to promote help to CD8+ T cells, but are also able to kill tumor cells directly (via MHC-class II dependent recognition) or indirectly (e.g., via the activation of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 143 publications
0
20
0
Order By: Relevance
“…As we all know, CD4 + T cells are important for the activation and expansion of CD8 + effectors, and also vital for the maintenance and generation of CD8 + T cell memory [ 8 ]. In the TME, they might also participate to amplify the CD8 + T cell response and have the ability to control tumor growth in different ways [ 8 ]. In our study, we found that CD4 + T cells were highly expressed in patient B but poorly expressed in patient C and patient D, implying that patient C and patient D had lower immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we all know, CD4 + T cells are important for the activation and expansion of CD8 + effectors, and also vital for the maintenance and generation of CD8 + T cell memory [ 8 ]. In the TME, they might also participate to amplify the CD8 + T cell response and have the ability to control tumor growth in different ways [ 8 ]. In our study, we found that CD4 + T cells were highly expressed in patient B but poorly expressed in patient C and patient D, implying that patient C and patient D had lower immunity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 ]. Tumor cells and the components of TME, including CD8 + T cells [ 6 , 7 ], CD4 + T cells [ 8 , 9 ], NK cells [ 10 ], dendritic cells [ 11 , 12 ], B cells [ 13 , 14 ], macrophages [ 15 ], FOXP3 [ 16 ], and Collagen I [ 17 ] have close correlations to tumor treatment and prognosis. In past decades, due to the limitations of tools and clinical methodologies, it was difficult to analyze multiple components and assess tumor heterogeneity of the TME.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of MHCII on the surface of APCs has a bound antigen peptide processed by the APC cells and the complex MHCII-bound peptide is recognized by the CD4 TCR that is specific for this complex. The interaction of the TCR and the MHCII complex results in the activation of the CD4 T cells along with co-stimulatory molecules on the APCs and the corresponding receptors on the CD4 T cells [10]. Naive T cells differentiate into one of several lineages of Th cells upon T cell receptor (TCR) activation, including Th1, Th2, Th9, and Th17 cells [9].…”
Section: Cd4 and Cd8 T Cellsmentioning
confidence: 99%
“…The literature has indicated that immunotherapy targeting PD-1 and CTLA-4 specifically increases CXCL9 and CXCL10 from tumor-associated macrophages in tumor tissues, whereas CXCL9 and CXCL10 are induced by IFNγ in the tumor microenvironment [27]. Therefore, another possibility for increasing CXCL9 in the nonCD8 + PBMCs was mediated by CD4 + T cells-secreted IFNγ since IFNγ is majorly secreted by CD4 + T cells, stimulated by antigen presenting cells [29].…”
Section: Discussionmentioning
confidence: 99%